2013
DOI: 10.1371/journal.ppat.1003315
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Adaptation of Candida albicans In Vivo Modulates Immune Recognition by Dectin-1

Abstract: The β-glucan receptor Dectin-1 is a member of the C-type lectin family and functions as an innate pattern recognition receptor in antifungal immunity. In both mouse and man, Dectin-1 has been found to play an essential role in controlling infections with Candida albicans, a normally commensal fungus in man which can cause superficial mucocutaneous infections as well as life-threatening invasive diseases. Here, using in vivo models of infection, we show that the requirement for Dectin-1 in the control of system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
160
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(170 citation statements)
references
References 48 publications
10
160
0
Order By: Relevance
“…Robinson et al found that BMDC from B6 mice required only 1 of the two Dectin receptors in order to make TNF-␣ and IL-10 in response to zymosan (83), implying that the function of the two receptors was redundant if a fungal particle is recognized by both receptors. Mutation of either receptor makes mice more susceptible to systemic Candida albicans infection, though this may depend on the strain of C. albicans used to infect the mice (31,84,85).…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al found that BMDC from B6 mice required only 1 of the two Dectin receptors in order to make TNF-␣ and IL-10 in response to zymosan (83), implying that the function of the two receptors was redundant if a fungal particle is recognized by both receptors. Mutation of either receptor makes mice more susceptible to systemic Candida albicans infection, though this may depend on the strain of C. albicans used to infect the mice (31,84,85).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of individual CLRs results in variable susceptibility to C. albicans (22,23) and A. fumigatus (24,43), in part due to strain-specific differences in CLR activation, as shown for C. albicans (59). Consistent with SYK/CARD9 being central for CLR signal integration, mice with hematopoietic or DC-specific Syk deletion or with global CARD9 deficiency are highly susceptible to C. albicans (29,60) and A. fumigatus (43) challenge.…”
Section: Introductionmentioning
confidence: 90%
“…Through its carbohydrate recognition domain, it specifically recognizes ␤-1,3-glucan (5), which is a typical component of fungal cell walls (6). Dectin-1 is considered a major receptor for ␤-glucans and plays an important role in the defense against various species of pathogenic fungi in mice, including Candida albicans, Aspergillus fumigatus, and Pneumocystis carinii (7)(8)(9)(10)(11). The importance of dectin-1 for antifungal defense has also been demonstrated by studies of human patients with disrupted dectin-1 function who display increased mucosal colonization with Candida species and suffer from recurrent mucocutaneous fungal infections (12,13).…”
mentioning
confidence: 99%